Readiness of young Malaysian fishermen to use global positioning system within the fishing operation - Osman, Mohd Nizam; Omar, Siti Zobidah; Bolong, Jusang; D' Silva, Jeffrey Lawrence; Mohamed Shaffril, Hayrol Azril (Canadian Center of Science and Education, 2014)
Global Positioning System or GPS is an advanced tool that has been widely used in a number of industries including fisheries industry. The main attempt of the present study has much to do with GPS as it aims to identify young Malaysian fishermen readiness to use GPS within their fishing operation. The study is quantitative in nature where a developed questionnaire was used to collect the required data. A total of 240 young fishermen aged between 15 to 40 years old from four fishing areas in Malaysia were selected as the respondents. Overall, it can be concluded that young Malaysian fishermen are ready to use GPS within their fishing operation. However, their readiness can be further improved if aspects such as financial affordability, number of agencies staff, availability of workshop repairing dysfunction GPS and access to GPS are considered by the related agencies.